Model Pertumbuhan Sapi Perah Friesian Holstein (FH) dari Lahir sampai Beranak Pertama di BBPTU-HPT Sapi Perah Baturraden Menggunakan Model Matematik Logistic - Ratnasari, D.; Atabany, A.; Purwanto, B. P.; Salma, L. B. (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2019)
This aims of this study is to first child by knowing growth model and creating a standard curve for dairy cattle growth at BBPTU-HPT Baturraden dairy cow in Baturraden district, Banyumas Regency, Purwokerto, Central Java. The data obtained form the primary data, were 353 tails and secondary data of births in 2005-2016 were 1437 tails and. Data were analyzed using SAS 9.4 program with NLIN procedures (Non Linear) using Logistic models. The results show that the Logistic model had a high degree of accuracy with the coefficient of determination (R2) 99.80%.